COVID-19 lockdown in South Africa: diction, Christian spirituality and mental health - De Backer, Lea M. (Verbum et ecclesia, 2021)
In attempting to manage and cope with the coronavirus disease 2019 (COVID-19) pandemic, varying health strategies were implemented by governments worldwide. The South African government passed legislation implementing a lockdown in the country which included a prohibition of the sale and transportation of alcohol and cigarettes. In this contribution, the impact of this legislation on the mental health of those in addiction and those in recovery was explored. Against the backdrop of the global political climate of COVID-19, factors influencing the concepts of health and healing were questioned. National online recovery groups were identified as interventions aimed at promoting a sense of community in the face of social isolation and social distancing. The integration of shared ideas between Christian theology and positive psychology relating to the concept of self-control was explored. Building forth on, ‘The interface of religion, spirituality and mental health in a South African context: Naming the unnamed conflict’ attitudes of collaboration between the two worlds of psychology and pastoral ministry included, amongst others, humility, integrity, honesty and teachableness. These attitudes were linked to underlying spiritual pillars of recovery evident in the Christian-based online recovery groups of Project Exodus.Intradisciplinary and/or interdisciplinary implications: These online recovery groups provided an example of an interdisciplinary approach to healing where psychology and Christian spirituality, as represented by mental health professionals, pastors and others in community, collaborated and encouraged the taking of personal responsibility, and supported the collective love, compassion and care towards those struggling with addiction, and those in recovery during the COVID-19 lockdown in South Africa.